Detrimental effect of UV-B radiation on growth, photosynthetic pigments, metabolites and ultrastructure of some cyanobacteria and freshwater chlorophyta. (1st February 2021) - El-Sheekh, Mostafa M.; Alwaleed, Eman A.; Ibrahim, Aml; Saber, Hani
Abstract: Background: Global warming directly influencing ozone layer depletion, which eventually is increasing ultraviolet radiation penetration having far-reaching impacts on living biota. This particularly influences the primary producer microalgae which are the basic unit of food webs in the aquatic habitats. Therefore, it is necessary to concentrate the research at this micro-level to understand the harmful impact of increased UV-B radiation ever before. Consequently, the present attempt aimed to focus on the influence of UV-B on growth criteria, photosynthetic pigments, some metabolites, and ultrastructure of the freshwater cyanobacteria, Planktothrix cryptovaginata (Microcoleaceae), Nostoc carneum (Nostocaceae), Microcystis aeruginosa (Microcystaceae), the Chlorophyte Scenedesmus acutus (Scenedesmaceae), and the marine Cyanobacterium Microcystis (Microcystaceae). Methods: The cultures of investigated algae were subjected directly to different duration periods (1, 3, 5, and 7 h) of artificial UV-B in addition to unirradiated control culture and allowed to grow for 10 days, after which the algal samples were analyzed for growth, photosynthetic activities, primary metabolities and cellular ultrastructure. Results: A remarkable inhibitory influence of UV-B was observed on growth criteria (measured as optical density and dry weight) and photosynthetic pigments of P. cryptovaginata, N. carneum, M. aeruginosa, S. acutus, and marine Microcystis . Where increasing the exposure time of UV-B was accompanied by increased inhibition. The variation in carbohydrate and protein contents under UV stress was based on the exposure periods and the algal species. The variation in algal ultrastructure by UV-B stress was noticed by an Electron Microscope. Cells damage and lysis, cell wall and cell membrane ruptured and release of intracellular substances, loss of cell inclusion, plasmolysis and necrosis, or apoptosis of the algal cells were observed by exposure to 7 h of UV-B. Conclusion: Exposure to UV-B has a marked harmful impact on the growth, pigments, and metabolic activity, as well as the cellular ultrastructure of some cyanobacteria and chlorophytes.